Characterization and Pathogenicity Evaluation of Ceratocystis sp. Isolated from Various Hosts on Acacia crassicarpa Seedlings - Lutfiana, Eva; Rahayu, Sri; Hardiyanto, Eko Bhakti; Indrioko, Sapto; Gafur, Abdul (Universitas Gadjah Mada, 2025)
Acacia crassicarpa is widely grown in forest plantations with Acacia mangium and Eucalyptus spp. Ceratocystis sp. is identified as a significant pathogen, causing substantial damage to A. mangium plantations as well as infecting A. crassicarpa, Eucalyptus spp., and several fruit trees such as Lansium spp., which led to yield losses. Research reported that isolates of Ceratocystis derived from various hosts have varying pathogenicity. Therefore, this research aimed to characterize the morphological properties and evaluate pathogenicity levels of eight Ceratocystis isolates (AC1, AC2, AM1, AM2, AM3, AM4, EP1, and LA1) on A. crassicarpa seedlings. The investigation occurred in the shade house and at the Faculty of Forestry UGM, Forest Health and Protection Laboratory in Yogyakarta. Four-month-old A. crassicarpa seedlings were artificially inoculated with Ceratocystis isolates from A. mangium, A. crassicarpa, Eucalyptus spp., and Lansium spp. hosts. The experiment employed a completely randomized design with four replicates. The results showed that characteristics of the isolates varied, but the differences in perithecium size were statistically insignificant. EP1 had a lighter color (greyish olive) than the other isolates. It was the most virulent and had a high potential for use in screening the resistance of A. crassicarpa clones against Ceratocystis sp. in the future.